Demographic Analysis of Occupational Safety in the Construction Sector: Strategies and Insights for Risk Reduction - Atiye Bilim (Buildings)
The construction sector is among the most dangerous industries, recognized for its significant rate of accidents with even more serious consequences, especially in developing countries. In addition to threatening the health and living conditions of workers, occupational accidents also negatively impact work productivity and sustainability. In this context, a country-by-country analysis of occupational accidents in the sector is critical to understand local demographic differences better and determine the impact of workplace safety practices. In parallel with the growing economy, the construction sector in Türkiye creates a large employment area and stands out as one of the sectors where occupational accidents occur most frequently. This study aims to analyze the interactions of occupational accidents and incapacity with demographic factors in the construction sector in Türkiye. This study analyzes the demographic factors, including age, gender, marital status, education, and work experience, of workers involved in occupational accidents within the construction industry between 2018 and 2022. As a result, it is found that young (18–27 years), male, single, and less experienced (1–10 years) workers are more prone to occupational accidents while increasing age and education level increases the risk of incapacity caused by occupational accidents. As experience increases, the probability of occupational accidents decreases; however, the recovery period is longer for workers who are exposed to heavy working conditions for a long time. The results show that the probability and severity of occupational accidents differ according to demographic characteristics. Therefore, high-risk workers should be identified, and occupational safety policies should be restructured based on this data. This study provides an important guide for policy changes and practical applications for demographically oriented restructuring of occupational safety measures in the construction industry.